2007
DOI: 10.1177/03946320070200s212
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Electromagnetic Fields on Immune and Nervous Responses

Abstract: In technologically developed countries, there is concern about hazards from electromagnetic fields (EMFs). Several studies have reported that immune and neuroendocrine systems exert an integrated response to EMF exposure. The aim of this review is to summarize the results of studies on the effect of low and high frequency EMF on immune and neuroendocrine systems on which our research group has been working for several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Studies have shown that EMFs could adversely affect reproductive outcomes and the immune system. [6][7][8][9][10][11][12][13][14][15] A recent study also…”
mentioning
confidence: 99%
“…Studies have shown that EMFs could adversely affect reproductive outcomes and the immune system. [6][7][8][9][10][11][12][13][14][15] A recent study also…”
mentioning
confidence: 99%
“…However, it is clear that the biological effects of EMFs may not be simply explained by the "thermal effects" only. The biological effects of EMFs depend on dose, time of exposure and frequency or wavelength (13). The energy of environmental EMFs absorbed by cells induces changes in metabolism; the effects of this interaction depend on the characteristic and excitability of the cells; it is known that environmental EMFs mainly affect the metabolic activities of nervous and immune cells (13).…”
Section: Effects Of Electromagnetic Fields On the Immune Systemmentioning
confidence: 99%
“…The biological effects of EMFs depend on dose, time of exposure and frequency or wavelength (13). The energy of environmental EMFs absorbed by cells induces changes in metabolism; the effects of this interaction depend on the characteristic and excitability of the cells; it is known that environmental EMFs mainly affect the metabolic activities of nervous and immune cells (13). In this review, we examine the results of studies on the effects of EMFs on immune and neuroendocrine systems which may exert integrated responses to environmental stimulations.…”
Section: Effects Of Electromagnetic Fields On the Immune Systemmentioning
confidence: 99%
“…The potential link between immune function, EMF exposure and EMF effect is unclear and immune suppressive as well as immune stimulatory effects have been reported in addition to the absence of effects. Moreover, in some exposure studies it was impossible to discriminate potential EMF effects, the effects of stress and potential pre-existing abnormalities [review by Boscolo et al, 2007].…”
Section: Inflammation (Crp Leucocytes Thrombocytes Mpv)mentioning
confidence: 99%